COMPETENCE OF VILLAGE APPARATUS: IS IT TRAINING MATERS? - Rohman, Arief; Zaenuri, Zaenuri; Rokhman, Fathur; Khafid, Muhammad (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2024)
The training that has been attended by village officials so far has not yielded optimal results. Meanwhile, training from various overseeing organizations is conducted annually. This study aims to investigate the role of motivation and perceived organizational support in mediating and moderating the impact of training on competence. The unit of analysis for this research is the village officials serving in all villages in Central Java Province, with a sample of 468 village officials determined using the Slovin method. Questionnaires were distributed based on the area random sampling method, and the data collected were analyzed using the SEM-PLS method with the WARP-PLS model. The results of the study show that both motivation and perceived organizational support mediate and moderate the impact of training on competence. Relevant organizations, including village governments, village empowerment services, and the Ministry of Villages, need to develop sustainable training policies and programs for village officials that are evaluated periodically.